Leading Lean Six Sigma : research on leadership for operational excellence deployment - Laureani, Alessandro; Antony, Jiju (Emerald Publishing Limited, 2021)
There is significant research available on critical success and failure factors of Lean Six Sigma implementation in organizations, predominantly focusing on the technical side of this performance method. But many organisations have overlooked soft skill aspects and the responsibilities of the Executive Leadership of the organization to make deployment a success. Leading Lean Six Sigma: Research on Leadership for Operational Excellence Deployment assesses the impact of organizational leadership on the deployment of Lean Six Sigma in organisations. By identifying leadership as a critical success factor for Lean Six Sigma deployment in organizations, this book details what leadership traits are needed for a successful deployment, differentiating by industry sector, and presents a ground-breaking leadership dependency model. Alessandro Laureani and Jiju Antony's new research extends and refines the current understanding of Lean Six Sigma and leadership, identifying the traits a leader needs to display to increase the chances of successful deployment. This book offers new perspectives for researchers examining Leadership, Management and Operational Excellence, as well as presenting useful guidance for practitioners launching, managing or sustaining continuous improvement initiatives in their organisations.
Includes index.
Keywords: Six sigma (Quality control standard); Lean manufacturing.; Leadership.; Business & Economics -- Industries / Manufacturing.; Manufacturing industries.; elektronické knihy; electronic books